2018
DOI: 10.1002/ca.23231
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density of human ear ossicles: An assessment of structure in relation to function

Abstract: Human ear ossicles are essential for normal sound conduction from the external environment to the inner ear. These bones are subjected to high biomechanical loads due to the sustained vibrations which occur with reception of sound. It is expected that the bones would undergo a significant amount of remodeling and change in bone mineral density during the lifespan of an individual. Therefore, the aim of the study was to evaluate the possible changes in bone mineral density of regions of the ossicular chain duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Thus, these sites are expected to have higher bone mineralization. The stapes footplate, which is in contact with the inner ear, has been found to have a higher density than other parts of the ossicles 4 . It is considered essential for effective sound transmission, as the higher density of the footplate allows an e cient coupling with the uid in the inner ear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these sites are expected to have higher bone mineralization. The stapes footplate, which is in contact with the inner ear, has been found to have a higher density than other parts of the ossicles 4 . It is considered essential for effective sound transmission, as the higher density of the footplate allows an e cient coupling with the uid in the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…Density affects their stiffness and mass, which in turn affects the ability to transmit sound. Unlike long bones, human auditory bones complete ossi cation shortly after birth, and little ossicular bone remodeling has been observed after that [2][3][4][5] . Recent studies have shown that the overall mineralization is much higher than in long bones 3 and that the density distribution within the ossicles is not uniform 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst some changes may be the result of general increases in size-associated growth, others may be the result of biomechanical influences. Assessments of bone density changes across various elements of the immature skeleton including the mandible [ 25 ] and ear ossicles [ 26 ] have proven useful in showing the potential effects of biomechanical influences on changes in the morphology of bones with growth. Hutchinson et al [ 25 ] in a sample of 45 mandibles aged between 30 gestational weeks and 5 years of age provided insights into the direction of growth of the mandible relative to dental eruption [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hutchinson et al [ 25 ] in a sample of 45 mandibles aged between 30 gestational weeks and 5 years of age provided insights into the direction of growth of the mandible relative to dental eruption [ 25 ]. Morris et al [ 26 ] showing a pattern of change in bone density relative to function across the ear ossicles illustrated how bone density patterns could be used to reflect changes in the functional environment [ 26 ]. These relationships between changes in bone mineral density patterns and growth of immature skeletal elements have provided valuable insights into how the morphology of the bone is influenced with age.…”
Section: Introductionmentioning
confidence: 99%